Relationship between 800-m running performance and running economy during high-intensity running in well-trained middle-distance runners - Fumiya Tanji; Toshiki Tsuji; Wataru Shimazu; Yasushi Enomoto; Yoshiharu Nabekura (Japanese Society of Physical Fitness and Sports Medicine, 2017)
Running economy (RE) at an intensity above the lactate threshold (LT) is reported to be the most important aerobic capacity for estimating 1,500-m running performance. The reason that the RE at intensity better reflects the energy metabolism during a 1,500-m run, is that it is performed above the LT intensity running. This study clarified the relationship between an 800-m run, which is performed above the LT intensity, and aerobic capacities, including the RE measured at intensities below and above the LT. This study included 12 well-trained male middle-distance runners (800-m velocity: 25.5 ± 0.5 km·h−1, LT intensity: 79.7 ± 5.1% maximal oxygen uptake [VO2max]). Both the RE of below and above the LT intensity were calculated at 65%VO2max (RE65) and 90%VO2max (RE90). The 800-m velocity was not related to the VO2max or the LT intensity (r = -0.16 and -0.10, respectively). This velocity correlated with both RE90 and RE65, with the correlation coefficient being higher for RE90 (r = -0.80 vs -0.75). Furthermore, the coefficient of determination for the 800-m velocity determined from VO2max, LT intensity and RE90 was higher than that determined from VO2max, LT intensity and RE65 (R2 = 0.522 vs 0.428, P = 0.03 vs 0.06). Based on these results, we concluded that the RE at an intensity above the LT might be better than other aerobic capacities for estimating the 800-m running performance, and more than 50% of this performance can be explained by VO2max, LT intensity and RE at an intensity above the LT.